2013
DOI: 10.1016/j.electacta.2013.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-anchored lithium vanadium oxide as anode of lithium ion battery

Abstract: Yi, J. et al. (2013). Graphite-anchored lithium vanadium oxide as anode of lithium ion battery. Abstract Graphite-anchored lithium vanadium oxide (Li1.1 V0.9 O2 ) has been synthesized via a "one-pot" in situ method. The effects of the synthesis conditions, such as the ratio of reaction components and calcination temperature, on the electrochemical performance are systematically investigated by means of scanning electron microscopy (SEM), X-ray diffraction (XRD), electrochemical impedance spectroscopy (EIS), ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…After 500 cycles at a rate of 2 C, the capacity of bare Li 1.1 V 0.9 O 2 and Li 1.1 V 0.9 O 2 /C microspheres is respectively 80 % and 95 % of the initial ones (Figure d). Compared with the previously reported literature (Figure e),,,, Li 1.1 V 0.9 O 2 /C microspheres exhibit a slight low capacity at 0.2 C rate, while reveal much higher capacity at other high rates.…”
Section: Resultscontrasting
confidence: 60%
“…After 500 cycles at a rate of 2 C, the capacity of bare Li 1.1 V 0.9 O 2 and Li 1.1 V 0.9 O 2 /C microspheres is respectively 80 % and 95 % of the initial ones (Figure d). Compared with the previously reported literature (Figure e),,,, Li 1.1 V 0.9 O 2 /C microspheres exhibit a slight low capacity at 0.2 C rate, while reveal much higher capacity at other high rates.…”
Section: Resultscontrasting
confidence: 60%
“…Recent studies have shown that Li can be intercalated into the layered oxide Li 1+x V 1Àx O 2 , at an unusually low voltage of B0.1 V vs. Li + /Li, [13][14][15][16][17][18][19][20] with a theoretical volumetric capacity of 1360 mA h cm À3 compared to graphite at 790 mA h cm À3 . Previously we investigated the intercalation process for Li 1+x V 1Àx O 2 and in particular the key role that non-stoichiometry or excess lithium (x 4 0) plays in switching on intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…Li-V-O layered compounds consist of LiVO 2 , LiVO 3 , LiV 2 O 5 , V 2 O 5 and derivatives of V 2 O 5 [38][39][40][41][42][43][44][45][46]. For a layered structure, the extraction of Li + ion and the migration of vanadium ions makes Li-V-O compound unstable, and easy to lose the diffusion path of lithium ions [47,48], which makes this compound suffer from severe capacitance loss during charging/discharging cycling.…”
Section: Introductionmentioning
confidence: 99%